O Senado e a política externa do governo do Partido dos Trabalhadores (2003-2012): a força do discurso parlamentar - Silva, Rodinei Tarciano (Universidade Federal de São Carlos, 2013)
This research aims to analyze the Brazilian Senate s Foreign Affairs Committee (CRE) according to the Discursive Institutionalism and the Political Discourse theories. This discursive study have sought to verify whether the CRE actually has an important institutional and discursive role in foreign policy making, which is typically deemed to be a preponderant power of the Executive branch, letting little room for the Legislative branch. This thesis argues that Brazilian foreign policy is public policy such as any else, even though foreign policy has the unique feature of usually being negotiated overseas by the Executive branch before the domestic political negotiation due to constitutional and organizational reasons. The methods of institutional analysis are deployed under a discursive perspective in order to demonstrate that the Brazilian Congress and its standing committees were endowed with legislative means of discursive participation in the foreign policy making, and, also, are analyzed the speeches of the senators to show that even those discursive means are subject to political discourse favoring the expansion and the improvement of their own efficacy, which presents the senators as interested participants in the foreign policy discussion. The CRE s political discourse also shows that political parties are important in that discussion, and they are analyzed in an ideological dimension in a left-right continuum in foreign policy done in this work and in their position inside congressional coalition groups, government or opposition. The speeches in the committee are researched through Discursive Textual Analysis on ideological (right-left) cleavage and on congressional coalition (government-opposition) cleavage, on the programmatic ideas of the political parties and on the specific political ideas in the metatexts made from the speeches about foreign affairs. The main results are: the CRE s political discourse has an intrinsically party matter, in which the ideas of the senators reverberate their party programmatic ideas during their coordinative discourse (inside the political instance), the importance of the discursive function of the Senate and of the CRE is crucial for foreign policy making, and the Brazilian foreign policy towards leftist regimes in Latin America was the main issue causing dissent in the committee between 2003 and 2012.
The brazilian Senate and the foreign policy of the worker s party administration (2003-2012): the strength of congressional discourse
Keywords: Ciência política; Discurso político; Institucionalismo discursivo; Partidos políticos; Brasil; Congresso; Senado; Política externa; Institucionalismo discursivo; Comissão de Relações Exteriores; Programas partidários; Ideias políticas; Análise textual discursiva; Political discourse; Discursive institutionalism; Foreign Affairs Committee; Foreign Policy; Political parties; Party programs; Political ideas; Discursive Textual Analysis; CIENCIAS HUMANAS::CIENCIA POLITICA